Analysis of Linguistic Terms in Mongolian Grammatical Works - Enkhjargal, Uranbileg; Davkharbayar (Mongolian Journal of Applied Linguistics, 2023)
With the development of Mongolian linguistic research, a specialized terminology denoting various phenomena in the Mongolian language has emerged. Numerous linguistic works, scientific literature, and textbooks extensively explore diverse aspects of the Mongolian language, employing general linguistic theories and methodologies for analysis. A meticulous elucidation of the structure, form, meaning, and usage of terms within these works is paramount for the study, teaching, and furtherance of linguistic research. Our focus, labeled as “Terms of Mongolian grammar” in this paper, pertains specifically to linguistic terminologies found within the four-volume works known as “Grammar of Mongolian Writing Language” (Mongol bičgiin helnii züi) by Academician Byambyn Rinchen. This research endeavor is an integral part of an ongoing research works aimed at constructing a comprehensive corpus of Mongolian linguistic works. Its objective is to facilitate the automatic recognition or identification of linguistic terms from these works by computational or automated means. In this study, we have formulated foundational criteria for identifying linguistic terms within the aforementioned four-volume works by Byambyn Rinchen. Additionally, we present research outcomes that entail the classification and thematic categorization of selected terms based on the prescribed criteria. Монгол хэл зүйн бүтээл дэх хэл шинжлэлийн нэр томьёоны шинжилгээ Хураангуй: Монгол хэл шинжлэлийн судалгаа үүсэн хөгжихтэй зэрэгцэн монгол хэлний үзэгдлийг заан нэрлэсэн нэр томьёо бий болсоор иржээ. Хэл шинжлэлийн ерөнхий онол, сургаалыг судалгааны үндэс, аргаа болгож, монгол хэлний олон янзын үзэгдлийг тал бүрээс нь шинжлэн туурвисан хэл зүйн бүтээл, эрдэм шинжилгээний ном зохиол, сурах бичиг олон буй. Тэдгээр бүтээлд буй нэр томьёоны бүтэц, хэлбэр, утга, хэрэглээг тодруулан судлах нь хэлний тухай шинжлэх ухааныг судлан шинжлэх, заан сургах, бүтээл туурвих зэрэгт чухал ач холбогдолтой билээ. Бидний өгүүлэлд голчлон хэрэглэх “монгол хэл зүйн нэр томьёо” гэсэн ухагдахуунд монгол хэл зүйн бүтээл дэх нэр томьёо, бүр тодруулбал Б.Ринчен Монгол бичгийн хэлний зүй дөрвөн боть бүтээлийн доторх “хэл шинжлэлийн нэр томьёо” гэсэн санааг илтгэж буй юм. Энэхүү судалгаа нь монгол хэл зүйн бүтээлийн хөмрөг байгуулж, түүн доторх нэр томьёог компьютерт автоматаар таниулах судалгааны нэг хэсэг болно. Тус өгүүлэлд Б.Ринчен Монгол бичгийн хэлний зүй дөрвөн боть бүтээлийн хөмрөгөөс нэр томьёог түүвэрлэн сонгох үндсэн шалгуурыг томьёолж, тухайн шалгуураар түүсэн нэр томьёог зүйлчлэн ангилсан судалгааны үр дүнг танилцуулжээ. Түлхүүр үг: хэл зүйн бүтээл, нэр томьёо, хэл шинжлэлийн нэр томьёо, монгол бичгийн хэлний зүй, хөмрөг хэл шинжлэл, хэл зүйн бүтээлийн хөмрөг